Athletes' perceptions of multilevel changes related to competing at the 2008 Beijing Olympic Games - Wylleman, P.; Reints, A.; Van Aken, S. (Psychology of Sport and Exercise, 2012)
Objectives: Taking into account the need for applied research on the most effective ways to prepare Olympians psychologically, the first purpose of this study was to gain more insight into the changes perceived by four athletes in view of their participation in the 2008 Beijing Olympic Games. The second purpose of this study was to illustrate how using a holistic and dynamic approach to the identification of the perceptions of these athletes' Olympic experiences can provide information relevant for the provision of individual ASP support to these athletes. Design: Using a prospective design athletes' perceptions of changes were gathered prior, during as well as after the Olympic Games. Methods: A combination of interview (pre and post Olympic Games) and self-reporting (during Olympic Games) was used to describe athletes' perceptions of changes occurring at athletic, psychological, psychosocial, academic/vocational level. Results: Results confirmed in first instance athletes' perceptions of the multifaceted nature of their Olympic experience. In second instance, the use of a dynamic and holistic perspective allowed to identify that participants perceived (a) during the phase prior to the Olympic Games 14 changes at all four levels, (b) during the Olympic Games eight changes at three levels, and (c) during the phase after returning from the Olympic Games 11 changes having occurred at four levels. Conclusions: This study showed the usefulness of using a dynamic and holistic perspective not only in order to identify athletes' perceptions of their Olympic experiences, but also to enhance ASP practitioners' knowledge on the needs for a holistic and dynamic ASP-support provision. In this way, the effectiveness and efficiency of ASP practitioners working with athletes preparing for, or competing at the Olympic Games could be enhanced.